Political Football Regulation, Globalization and the Market. - Wyn, Grant (Agenda Publishing, 2021)
"The state's presence in professional football has been ad hoc and inconsistent. Football has been largely exempt from the development of the regulatory state and has been left to govern itself. However, new media have raised the profile of the game and globalization has created new pressures as clubs become pawns in the ambitions of states and wealthy individuals. Clubs offer an important sense of identity for fans, but the impersonality and distance of ownership can set up new tensions. Corruption in the international governing body has been a significant problem and the sport's symbiotic relationship with gambling is a concern. There are no off-the-shelf solutions for regulation, but clearly, the complexities of the beautiful game and its economic size require more attention from government."--Amazon.